Crystal structure of the human cytomegalovirus pUL50-pUL53 core nuclear egress complex provides insight into a unique assembly scaffold for virus-host protein interactions - Walzer, Sascha; Egerer-Sieber, Claudia; Sticht, Heinrich; Sevvana, Madhumati; Hohl, Katharina; Milbradt, Jens; Muller, Yves; Marschall, Manfred (Journal of Biological Chemistry, 2015)
Nuclear replication of cytomegalovirus relies on elaborate mechanisms of nucleocytoplasmic egress of viral particles. Thus, the role of two essential and conserved viral nuclear egress proteins, pUL50 and pUL53, is pivotal. pUL50 and pUL53 heterodimerize and form a core nuclear egress complex (NEC), which is anchored to the inner nuclear membrane and provides a scaffold for the assembly of a multimeric viral-cellular NEC. Here, we report the crystal structure of the pUL50-pUL53 heterodimer (amino acids 1-175 and 50-292, respectively) at 2.44 Å resolution. Both proteins adopt a globular fold with mixed α and β secondary structure elements. pUL53-specific features include a zinc-binding site and a hook-like N-terminal extension, the latter representing a hallmark element of the pUL50-pUL53 interaction. The hook-like extension (amino acids 59-87) embraces pUL50 and contributes 1510 Å to the total interface area (1880Å). The pUL50 structure overall resembles the recently published NMR structure of the murine cytomegalovirus homolog pM50 but reveals a considerable repositioning of the very C-terminal α-helix of pUL50 upon pUL53 binding. pUL53 shows structural resemblance with the GHKL domain of bacterial sensory histidine kinases. A close examination of the crystal structure indicates partial assembly of pUL50-pUL53 heterodimers to hexameric ring-like structures possibly providing additional scaffolding opportunities for NEC. In combination, the structural information on pUL50-pUL53 considerably improves our understanding of the mechanism of HCMV nuclear egress. It may also accelerate the validation of the NEC as a unique target for developing a novel type of antiviral drug and improved options of broad-spectrum antiherpesviral therapy.

High-resolution crystal structures of two prototypical β- And γ-herpesviral nuclear egress complexes unravel the determinants of subfamily specificity - Muller, Yves; Häge, Sigrun; Alkhashrom, Sewar; Höllriegl, Tobias; Weigert, Sebastian; Dolles, Simon; Hof, Kerstin; Walzer, Sascha; Egerer-Sieber, Claudia; Conrad, Marcus; Holst, Stephanie; Lösing, Josephine; et al. (Journal of Biological Chemistry, 2020)
Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric basic structure of the nuclear egress complex (core NEC). These core NECs serve as a hexameric lattice-structured platform for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina- and membrane-rearranging functions (multicomponent NEC). Here, we report the X-ray structures of β- and γ-herpesvirus core NECs obtained through an innovative recombinant expression strategy based on NEC-hook::NEC-groove protein fusion constructs. This approach yielded the first structure of γ-herpesviral core NEC, namely the 1.56 Å structure of Epstein-Barr virus (EBV) BFRF1-BFLF2, as well as an increased resolution 1.48 Å structure of human cytomegalovirus (HCMV) pUL50-pUL53. Detailed analysis of these structures revealed that the prominent hook segment is absolutely required for core NEC formation and contributes approximately 80% of the interaction surface of the globular domains of NEC proteins. Moreover, using HCMV::EBV hook domain swap constructs, computational prediction of the roles of individual hook residues for binding, and quantitative binding assays with synthetic peptides presenting the HCMV- and EBV-specific NEC hook sequences, we characterized the unique hook-into-groove NEC interaction at various levels. Although the overall physicochemical characteristics of the protein interfaces differ considerably in these β- and γ-herpesvirus NECs, the binding free energy contributions of residues displayed from identical positions are similar. In summary, the results of our study reveal critical details of the molecular mechanism of herpesviral NEC interactions and highlight their potential as an antiviral drug target.
CRIS-Team Scopus Importer:2020-03-17